Outstanding phenotypes of Pinus chiapensis and Pinus douglasiana in forest management stands in Oaxaca - Cervantes-Machuca, María Mercedes; Rodríguez-Ortiz, Gerardo; Santiago-García, Wenceslao; Enríquez-del Valle, José Raymundo; Campos-Angeles, Gisela Virginia (Ecosistemas y Recursos Agropecuarios, 2024)
In some areas of Oaxaca, Mexico, it is necessary to implement plantations that use seeds of genetic quality, to increase productivity and phenotypic quality. The objective was to select outstanding phenotypes of Pinus chiapensis (Martínez) Andresen and P. douglasiana Martínez, evaluating quantitative and qualitative characteristics. In 2021, 15 superior phenotypes per species were selected to evaluate inventory variables (height, diameter), density (trees ha-1), age and chip increments, recording climate and site data. Crown area (m2), basal area (m2) and total volume with bark (VTcc, m3) were determined for each tree; site index (SI) was determined based on anamorphic curves, density guides and average VTcc. Data were analyzed with Student’s t tests, Pearson’s correlation (a = 0.05), cluster analysis, and principal component analysis. The species showed significant differences (p ≤ 0.01) in dasometric characteristics. Using the average volume as a selection criterion, six P. chiapensis trees presented volumes above average (≥ 9.76 m3) and seven P. douglasiana trees presented volume above average (> 4.14 m3) and clear stem height (18.7 m), in places with high precipitation; while comparing morphological, of site and climatic characteristics, 10 individuals of P. chiapensis and six of P. douglasiana with excellent quality IS were selected. The selected trees have outstanding characteristics of wood quality and volume, so it is convenient to use them to collect seeds in the study area.